APPLICATION OF 3D PHOTOGRAMMETRY TECHNIQUES AND ACCURACY EVALUATION IN MEASURING CORAL REEF VOLUME IN THE NORTHERN WATERS OF TUNDA ISLAND - Wardono, Suko; Athaillah, Ibnu; Handayani, Endy; Rosalina, Dwi; Rizkiah, Riza (Politeknik Kelautan dan Perikanan Karawang, 2026)
This study explores the application of underwater 3D photogrammetry and accuracyevaluation in measuring coral reef volume in the northern waters of Tunda Island. The global decline in coral populations—due to environmental stressors such as rising sea temperatures, predation, and destructive human activities— necessitates accurate and non-destructive monitoring methods. 3D photogrammetry allows digital recording of coral shapes in three dimensions by processing underwater images using Agisoft Metashape and analyzing volume through MeshLab. The research focuses on three coral growth forms: branching, massive, and foliose, using varying numbers of photos (50, 100, 150, 200, and 250) to assess their impact on model accuracy. Results indicate that while more photos generally improve accuracy, this relationship is not always linear. For example, foliose corals showed a slight decrease in accuracy at 250 photos due to increased error points. Volume values remained relatively consistent despite accuracy variations. Several factors influenced reconstruction accuracy, including light conditions, water turbidity, current velocity, and camera positioning. Among all photo counts, 150 photos emerged as the most ideal—offering high accuracy with significant efficiency in data acquisition, storage, and processing time. This optimal balance makes it suitable for repeated monitoring efforts. In conclusion, this study demonstrates that underwater 3D photogrammetry is a practical and effective method for coral growth assessment. It supports the development of sustainable coral reef monitoring techniques that provide detailed, repeatable, and non-invasive data, crucial for marine conservation efforts.